2019
DOI: 10.28991/cej-2019-03091223
|View full text |Cite
|
Sign up to set email alerts
|

Stress Concentration Factors (SCFs) in Circular Hollow Section CHS-to-H-shaped Section Welded T-Joints under Axial Compression

Abstract: The aim of this paper is to investigate the effects of non-dimensional geometric parameters on stress concentration factors (SCFs) of circular hollow section CHS brace-to-H-shaped section T-connections under axial compression. This type of welded joints is used increasingly in steel construction. However, its fatigue design is not covered by codes, and its fatigue strength has not been given the deserved attention by researchers.  This research, however, bridges the gab on SCFs in this type of welded connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The main result was that the stress distribution is characterized by stress peaks at the edges of the bonded region. Hamdan [8] analysed the effects of nondimensional geometric parameters on stress concentration factors of circular hollow section brace-to-H-shaped section T-connections under axial compression. Rastegarian et al [9] studied the dependency of structural performance level and its corresponding inter-story drift in conventional RC moment frames.…”
Section: Introductionmentioning
confidence: 99%
“…The main result was that the stress distribution is characterized by stress peaks at the edges of the bonded region. Hamdan [8] analysed the effects of nondimensional geometric parameters on stress concentration factors of circular hollow section brace-to-H-shaped section T-connections under axial compression. Rastegarian et al [9] studied the dependency of structural performance level and its corresponding inter-story drift in conventional RC moment frames.…”
Section: Introductionmentioning
confidence: 99%
“…Loy et al [20] studied the free vibration of functionally classified (St-Ni) cylindrical shells and the influence of constituent volume fractions on natural frequencies. Hamdan [21] investigated the effects of non-dimensional geometric parameters on stress concentration factors (SCFs) of circular hollow section CHS brace-to-H-shaped section T-connections under axial compression. The results showed that SCFs in the brace and chord increases.…”
Section: Introductionmentioning
confidence: 99%